Desenvolvimento de microcápsulas contendo as antocianinas presentes no corante do extrato do jambo por polimerização interfacial - Maia, Juliana Leão (2013)
The industries of food, medicine and cosmetic apply microencapsulation for many reasons, among them, stabilize the active, control the release of encapsulated and separate incompatible components of the formulation. In this context, microencapsulation techniques have been used in the food industry to provide stable liquid and solid ingredients. Anthocyanins have high antioxidant potential, but they are photodegradable. The challenges are therefore directed to the research for techniques that could make this potential remaining active and bioavailable and could be used as a vehicle for the delivery release of bioactive and micronutrients in appropriate conditions and levels. This work has as main objective to propose a method to encapsulate the anthocyanins in the extract of mountain apple using the interfacial polymerization technique. As well as to define the ideal conditions of temperature and agitation system for this procedure. The microparticles were characterized for size, morphology, active distribution, surface charge, degradation, composition and stability. The results, like particle diameter of 5.94 μm and Zeta potential of 7.03 mV, showed that the technique used to obtain these microparticles was satisfactory and has potential for application in cosmetics and food